Disparities in moderate-to-vigorous physical activity among girls and overweight and obese schoolchildren during school- and out-of-school time - Hubbard, Kristie (Int J Behav Nutr Phys Act, 2016)
BACKGROUND: Increasing physical activity (PA) during the school day and out-of-school time are critical strategies for preventing childhood obesity and improving overall health. The purpose of the present investigation was to examine schoolchildren’s volume and type of PA during school-time and out-of-school, compared to national recommendations and differences by sex and weight status. METHODS: This cross-sectional analysis included 517 3(rd)-5(th) grade schoolchildren from 13 New England elementary schools (October 2013-January 2014). Demographics were collected by parent questionnaire. Measured height and weight were used to categorize child weight status. Accelerometer data were collected over 7 days. PA was coded as total activity counts and minutes of sedentary, light, and moderate-to-vigorous physical activity (SED, LPA, MVPA) during 1) school, 2) weekday out-of-school, 3) weekend, and 4) total daily time. Multivariable mixed models were used to examine associations between sex and weight status and total counts, SED, LPA, and MVPA, controlling for demographics, wear-time, and clustering within schools. RESULTS: 453 participants (60.5 % girls; mean age 9.1 years; 30.5 % overweight/obese) had valid accelerometer wear time (≥3 days, ≥ 10 h/day). Few children achieved 60 min total daily (15.0 %) or school-time (8.0 %) MVPA recommendations. For all time-of-day categories, girls achieved fewer MVPA minutes than boys (p < .0001), and overweight/obese participants achieved fewer MVPA minutes than normal/underweight participants (p = 0.05). Minutes of LPA declined by grade-level (p < .05) and were lower in girls than boys during school-time only (p < .05). CONCLUSION: Disparities in MVPA by sex and weight status across school and out-of-school time highlight the need for programs with equitable reach.